2019
DOI: 10.1093/eurheartj/ehz746.0296
|View full text |Cite
|
Sign up to set email alerts
|

P5327Are we being able to meet current guidelines LDL-cholesterol goals in very high risk patients? How many of them could benefit of PSCK9 inhibition by the FOURIER/ODYSSEY and NICE criteria?

Abstract: Background/Introduction With increasing evidence of LDL-cholesterol (LDL-c) lowering and a subsequent reduction in cardiovascular events, guidelines of different parts of the world aim for lower LDL-c goals by risk stratification. Proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibition has been able to reduce up to 60% LDL-c levels, with further reduction in cardiovascular outcomes. Purpose Our aim was to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the randomized HPS2-THRIVE trial of niacin-laropiprant versus placebo, on a background of simvastatin therapy, the authors have concluded that novel therapies that reduce high Lp(a) levels by at least 80 nmol/L (≈40%) may be needed to produce worthwhile benefits in people at the highest risk because of Lp(a) 8 . Current options for treatment of high Lp(a) are limited to the Proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors, which have been shown to reduce the levels by 25-30% on average, with or without background statin therapy 1,9,10 . Patients treated with PCSK9 in a study from Denmark do not resemble the populations from the major endpoint studies, as the majority of this real-life population is statin intolerant.…”
Section: Cardiovascular Risk Categoriesmentioning
confidence: 99%
“…In the randomized HPS2-THRIVE trial of niacin-laropiprant versus placebo, on a background of simvastatin therapy, the authors have concluded that novel therapies that reduce high Lp(a) levels by at least 80 nmol/L (≈40%) may be needed to produce worthwhile benefits in people at the highest risk because of Lp(a) 8 . Current options for treatment of high Lp(a) are limited to the Proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors, which have been shown to reduce the levels by 25-30% on average, with or without background statin therapy 1,9,10 . Patients treated with PCSK9 in a study from Denmark do not resemble the populations from the major endpoint studies, as the majority of this real-life population is statin intolerant.…”
Section: Cardiovascular Risk Categoriesmentioning
confidence: 99%